The Impact of Artificial Aging on the Color Stability and Hardness of Nanocomposite Resin - Wang, Likai; Zheng, Yan (Frontiers in Materials, 2021)
Objective: This study aimed to investigate the impact of artificial aging on the color stability and hardness of nanocomposite resin. Methods: Four nanocomposite resin materials were used: Filtek Z350 XT (FZ), Synergy D6 (SD), Grandio (GD), and Clearfil Majesty Esthetic (CM). Thirty specimens were created from each material, which were divided into three groups of 10 specimens each. These groups were recorded as group A, group B, and group C, and a total of 120 specimens were made. For each material, the values of visual lightness (L*), degree of redness and greenness (a*), and degree of yellowness and blueness (b*) of the specimens in group A, as well as the hardness of the specimens in group B, were measured. The group A and group C specimens were then artificially aged, after which the values of L*, a*, and b* of the group A specimens and the hardness of the group C specimens were measured. The color difference (ΔE00) value and hardness difference (ΔH) value of the specimens before and after aging were calculated. Results: Aging was found to have an impact on the ΔE00 values of the resin materials in each group (F = 29.221, P = 0.000), and the hardness of the specimens in each group after artificial aging was significantly higher than before aging (P < 0.05). The hardness of the specimens in each group after aging was significantly higher than before aging (P < 0.05). The results show that aging had an impact on the ΔE00 values in each group (F = 29.221, P = 0.000). The difference in ΔE00 between the FZ group and the SD, GD, and CM groups was statistically significant (P < 0.05). There was no correlation between ΔE00 and the hardness change percentage after aging (r = 0.114). Conclusion: There have been many previous studies on the color stability and hardness of composite resins, but few have explored the relationship between them. The results of the present study revealed that there was no correlation between ΔE00 and hardness change percentage in the four nanocomposite resin materials after aging.